Multivariate Analysis of Thermal Adaptive Profile of Three Genetic Groups of Duck - Abel Oguntunji; Opeyemi Adetola Oladejo; Mathew Oluseyi Ayoola; Lopemi Opeoluwa Oriye; Opeyemi Olufemi Ogundijo; Abiola Olufunke Ilufoye (Buletin Peternakan, 2020)
Inherent thermal adaptation in livestock is an important economic trait that cannot be overlooked, most especially in animals reared in sub-optimal thermally stressful environments. The present study explored the possibility of using multifactorial discriminant analysis (DA) to separate two duck genera {Muscovy and Common (Mallard) ducks) and their hybrid (Mule ducks) to distinct genetic groups using physiological, haematological and biochemical parameters. Data were collected after exposure of ducks to solar radiation for 90 minutes (12.00 – 13.30 hours). The result of analysis of variance indicated that genotype significantly (P<0.05) affected heamoglobin (Hb), basophil (Bas), total protein (TP), albumin (Alb), globulin (Glb), skin temperature (SKT), respiratory rate (RRT), panting rate (PTR) and rectal temperature (RTC). Stepwise DA revealed that PTR, RRT, Bas and TP in descending order were the most important parameters discriminating the three duck genotypes. The result of cross validation showed that 71.00%, 97.30% and 50.00% of Muscovy, Common and Mule ducks were correctly classified in their expected genetic group respectively. The Euclidean distance between the duck genotypes indicated that longest distance (86.507) was between Muscovy and Common (Mallard) ducks while shortest distance (12.415) was between Muscovy and Mule ducks. The results are applicable in breed adaptation studies, management, conservation and improvement programmes.